Romance de ditador: a insurgência de Roa Bastos em Eu, O Supremo - Nardini, Douglas (2024)
The main objective of this research is to analyze the character created by Augusto Roa Bastos (1917-2005), the Supremo, to refer to the perpetual dictator José Gaspar Rodríguez de Francia, in the novel I, the Supremo (1974). Roa Bastos is one of the most important names in Paraguayan literature and his main work is centered on the history of the dictatorial regime of the government of José Gaspar Rodríguez de Francia, from 1814 to 1840, whose narrative constructs a possible version of Paraguay's national identity. As for methodological processes, it corresponds to research of a basic nature, exploratory in terms of its objectives, bibliographic in terms of its technical procedures and qualitative in terms of its approach. The main theoretical basis is the contributions of Navarro (1989), Menton (1993), Zilberman (2003), White (1995) and Ricoeur (2019). With this, we seek, through the relationship between Literature and History, to problematize aspects of Paraguayan national identity and construct an analysis of the aspects that characterize the historical novel in Latin America; of the historical matter that is the theme of the studied novel and; finally, the construction of the protagonist character of the narrative. The results of the investigation indicate that the fictional narrative refers to a story that happened in Paraguay, creating credible actions that clearly recall events from a period of dictatorship in the country, highlighting the representation of History through the Supreme Court's way of acting and thinking. Dictator.